The Association of Malignancies with The Clinical Profile of Children with Neurofibromatosis Type 1 - Nihal Sahin; Ugur Demirsoy; Funda Corapcioglu (Galenos Publishing House, 2022)
Neurofibromatosis type 1 (NF-1) is a significant autosomal dominant disorder with a wide spectrum of clinical findings. These signs (Café au lait spots, bone dysplasia, Lisch nodules) usually start to emerge after the first months of life and most are benign in nature. On the other hand, neoplasms (optic glioma, neurofibroma, malignant peripheral nerve sheath tumor, soft tissue sarcoma, leukemia, breast cancer) are a major cause of morbidity and mortality in NF-1 patients. Cancer risk during the lifetime of an NF-1 patient is almost 10 times more than a person without NF-1, but what drives these patients into cancer is still unknown. This study aims to analyze the possible association of clinical findings with malignancies in children with NF-1. Medical records of 55 children with NF-1 who were followed up in a tertiary care pediatric oncology clinic between January 2005 and December 2014 were analyzed. We assessed clinical and demographic characteristics of patients, as well as the NF-1 diagnostic criteria, NF-1 related complications, and malignancies. The NF-1 patients without malignancy were classified in Group 1 while patients with malignancy were in Group 2. Logistic regression analysis was used to determine the risk factors of malignancy in NF-1. The mean age was 7.68 ± 4.65 years. Female sex was dominant in both groups. Café au lait spots were present in all patients. Axillary-inguinal freckling was observed in 76.4% of patients, followed by neurofibromas in 30.9%, Lisch nodules in 29.1%, bone dysplasia in 14.5%, optic gliomas in 23.6%, and a history of first degree relative with NF-1 in 63.6%. Central nervous system (CNS) tumors were present in 40%. Tumors other than CNS tumors were acute myeloid leukemia and schwannoma. None of the diagnostic criteria was a risk factor for predisposing to malignancy by itself. Having >3 criteria was found to be the risk factor for malignancy in NF-1 (OR:5.891, CI 95%: 1.676-20.705, p=0.006). There are no clearly defined risk factors predicting occurance of malignancies in NF-1 at present. However, we found a higher risk of malignancy association in patients who meet more than 3 diagnostic criteria of NF-1.